Balancing Life and Integrity: The Role of Good Governance and Public Trust in Employee Performance through Job Satisfaction - Krismanto, Yudha Parna; Juhandi, Nendi; Winarto, Pawit (Human Capital and Organizations, 2025)
This study aims to analyze the influence of work-life balance, good governance, and perceived public trust on employee performance, with job satisfaction as a mediating variable. This study used a survey method, distributing questionnaires via Google Forms to 105 employees at the Kalisari Village Office in East Jakarta, using a simple random sampling technique. Data analysis was conducted using SmartPLS. The results showed that work-life balance and good governance significantly influenced job satisfaction, while perceived public trust did not. Furthermore, job satisfaction significantly influences employee performance. Work-life balance had both direct and indirect effects on employee performance through job satisfaction. In contrast, good governance and perceived public trust did not significantly influence employee performance, either directly or through job satisfaction. The implications of this study confirm that work-life balance is a key factor in improving employee satisfaction and performance. While the application of good governance principles and public perception requires strengthening to have a greater impact on the governance apparatus.